2011
DOI: 10.9710/kjm.2011.27.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Productivity of a Polyculture Container for Suspended Rearing of Abalones and Sea cucumbers

Abstract: We have developed a polyculture container which is preferable for rearing of abalones and sea cucumbers in East Sea. To test the rearing capacity of the polyculture container, 50, 75 and 100 sea cucumbers ranging from the body length of 7-9 cm were cultured in three containers including 500 abalones with the shell length of about 5 cm, respectively. It was revealed that preferable density for sea cucumbers was 52-72 individuals in the polyculture container. Glutamate oxaloacetate transaminase and glutamate pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the study of Oh et al (2013) the maximum distance of movement was 0.75 m at a water temperature of 10 °C, 0.1 m at 13 °C, and 0.2 m at 19 °C. Nam, Lee, Moon, Kim & Hwang (2011) carried out an experimental polyculture of abalone and sea cucumber and found that sea cucumbers grew at an average monthly rate of 5.4 g in the east coast type of farm and at an average monthly rate of 4.8 g in the south coast type. The present study showed a continual growth without estivation, which was assumed to be because the animals were reared at temperatures below 20 °C at a depth of 15 m. Lee, Gil, Lee, Kim & Hur (2018) presented that sea cucumbers with an average weight of 2.3 g grew to 12.5 g in an experimental area of reefs after 1 year with a specific growth rate of 0.03 g/day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Oh et al (2013) the maximum distance of movement was 0.75 m at a water temperature of 10 °C, 0.1 m at 13 °C, and 0.2 m at 19 °C. Nam, Lee, Moon, Kim & Hwang (2011) carried out an experimental polyculture of abalone and sea cucumber and found that sea cucumbers grew at an average monthly rate of 5.4 g in the east coast type of farm and at an average monthly rate of 4.8 g in the south coast type. The present study showed a continual growth without estivation, which was assumed to be because the animals were reared at temperatures below 20 °C at a depth of 15 m. Lee, Gil, Lee, Kim & Hur (2018) presented that sea cucumbers with an average weight of 2.3 g grew to 12.5 g in an experimental area of reefs after 1 year with a specific growth rate of 0.03 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that this study will contribute to increase income of aquaculture farmers and it would help to improving the environment of aquaculture farms. There are numerous studies on the sea cucumber polyculture using abalones, oysters and scallops which were designed to identify the function of sea cucumbers to feed on organic matter and wastes produced by different farmed animals (Paltzat, Pearce, Barnes & Mckinley, 2008;Nam, Lee, Moon, Kim & Hwang, 2011;Li, Dong, Gao & Zhu, 2014). Yu, Zhou, Yang, Ma & Hu (2014) studied polyculture of fish and sea cucumbers by placing sea cucumber nets under the bottom of a fish cage.…”
Section: Analysis On Inhabitation Densities Of Sea Cucumber In the Pomentioning
confidence: 99%
See 1 more Smart Citation